Taxonomic revision of the Nylanderia guatemalensis species complex (Hymenoptera: Formicidae) in the Neotropics, with implications for conservation and invasion biology - Williams, Jason L.; Puckett, Corbin; Herrera, Henri W.; Lapolla, John S.; Fiorentino, Gianpiero; Tocora-Protz, María Camila; Fernández, Fernando; Dekoninck, Wouter; Lucky, Andrea (Zootaxa, 2026)
The ant genus Nylanderia Emery comprises 138 known species and is common across most terrestrial regions worldwide. At least 15 species have spread beyond their native ranges, some becoming ecologically and economically destructive. Subtle morphology, unresolved taxonomy, and widespread distributions make these species difficult to identify, complicating conservation efforts in biodiversity hotspots like the Galápagos Islands. Here, based on a comprehensive examination of Neotropical Nylanderia, we revise the taxonomy of the N. guatemalensis complex, recognizing seven described species: N. ambulator Williams et al.; N. coveri LaPolla & Kallal; N. docilis (Forel); N. guatemalensis (Forel); N. insularis Williams sp. nov.; N. nesiotis (Wheeler) stat. nov.; and N. silvestrii (Emery); plus an undescribed eighth, N. sp. JKW1 (singleton). Among these, we confirm two in the Galápagos: the non-native N. guatemalensis and the endemic N. nesiotis. While eight other ant species in the Galápagos are considered probable endemics, N. nesiotis is the first confirmed as such. We synonymize N. lietzi (Forel), N. steinheili (Forel), N. guatemalensis cocoensis (Forel), N. guatemalensis itinerans (Forel), and N. silvestrii kuenzleri (Forel) with N. guatemalensis, and N. guatemalensis edenensis (Linsley & Usinger) with N. nesiotis. Species boundaries are supported by combined evidence from Ultraconserved Element (UCE) phylogenomics and morphology. We provide distributions, a worker-based key, and high-resolution images of available castes to facilitate species recognition, support biodiversity monitoring, and improve detection and management of invasive Nylanderia.